1985
DOI: 10.1063/1.335649
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous phase separation in polypropylene block copolymers as revealed by thermostimulated depolarization measurements. II. Thermal sampling analysis

Abstract: We achieved a thermal sampling scanning of the β-relaxation region of polypropylene (PP) block copolymers together with the β process of isotactic polypropylene, high-density polyethylene, propylene-ethylene rubber, and part of the PP bloc copolymer soluble in xylene and insoluble in ether. The comparison of activation parameters determined in the above relaxations confirmed the hypotheses drawn from complex spectra studies concerning phase separation and the origin of dielectric relaxations in PP block copoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…For all the samples only two linear behaviors (compensation rules) are observed. As expected in polymers investigated by thermally stimulated techniques, 8,10,16,22,[26][27][28][29][30][33][34][35] a well-defined linear relationship between ∆S and ∆H is observed for the TSCR R peak associated with the glass transition (defined as the temperature range where the drastic increase of enthalpy occurs), independent of the microstructure. The elementary processes isolated in the temperature range before the drastic increase of ∆H lead to a separate compensation law as well.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…For all the samples only two linear behaviors (compensation rules) are observed. As expected in polymers investigated by thermally stimulated techniques, 8,10,16,22,[26][27][28][29][30][33][34][35] a well-defined linear relationship between ∆S and ∆H is observed for the TSCR R peak associated with the glass transition (defined as the temperature range where the drastic increase of enthalpy occurs), independent of the microstructure. The elementary processes isolated in the temperature range before the drastic increase of ∆H lead to a separate compensation law as well.…”
Section: Resultssupporting
confidence: 62%
“…As shown in S-90 PMMA, a linear relationship exists between Δ S and Δ H for several FL-TSCR elementary processes. This relationship is well-known as the compensation rule ,,,,, and can be written as where S 0 is a constant. For all the samples only two linear behaviors (compensation rules) are observed.…”
Section: Resultsmentioning
confidence: 99%
“…The TSC thermal sampling (TSC-TS) or thermal windowing technique has been applied to polymers showing the capability of resolving complex dielectric transitions into narrow distributions of relaxations. [6][7][8][9][10][11][12][13][14][15][16] Reviews including very recent ones are available. [17][18][19][20][21][22] Several studies of the glass transition region in PMMA have been reported, 11,17,18,[22][23][24][25] including reports where the TSC-TS technique was applied.…”
Section: Introductionmentioning
confidence: 99%
“…The TSC thermal sampling (TSC-TS) or thermal windowing technique has been applied to polymers showing the capability of resolving complex dielectric transitions into narrow distributions of relaxations. Reviews including very recent ones are available. Several studies of the glass transition region in PMMA have been reported, ,,,− including reports where the TSC-TS technique was applied. ,− In general, explanations for the TSC-TS results and the relationship of the activated parameters to glass transition phenomena are somewhat controversial. ,,, It is known that the TSC-TS method is uniquely sensitive in the case of weak or overlapping relaxations, where one can resolve “cooperative relaxations”, e.g., those corresponding to high values of the apparent activation energy E a , even if the species are a minor fraction of the overall relaxing species. , This high sensitivity to the high activation energy relaxing species is related mainly to the polarization and depolarization sequences used, and the method used for extracting E a from the TSC-TS peaks, and will be discussed more quantitatively in a future report . In this report we characterize the broad glass transition regions of PMMA of different tacticities in terms of the magnitude of the values of E a .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the practical significance of the compensation parameters appearing in thermally stimulated studies is difficult to interpret and up to now no consistent theory has offered an unambiguous explanation for their physical origin. Various interpretations of the compensation phenomenon can be found in the literature, e.g., it has been considered as an indicator of cooperative molecular motions or some other cooperative transitions (48,53,(57)(58)(59), explained in terms of the coupling model by Marchal (60,61), who suggested that T c could be related to a phase transition temperature (57,62), or explained as an information transfer between the two thermokinetic parameters by means of some kind of thermal mechanism (63,64). The difference between T c and T g has been related to the stiffness of the polymeric chain (8), though this relation is not very clear as shown by Ramos et al (65).…”
Section: Molecular Mobility In Polymersmentioning
confidence: 99%